Analysis and Design of Entrepreneurship Information System as Student Business Unit Marketplace (Case Study: Universitas Pembangunan Nasional “Veteran” East Java) - Arista Pratama; Siti Mukaromah; Syurfah Ayu Ithriah; Rizky Parlika (Future Science)
Universities as higher education institutions are obliged to produce graduates who have an entrepreneurial activities and are highly competitive. Universitas Pembangunan Nasional Veteran Jawa Timur is one of the state universities that encourages and supports the potential of entrepreneurial activities by providing entrepreneurship courses to all students. The problem is the student business units that have been built during the courses did not develop even stopped due to the unavailability of facilities to accommodate the entrepreneurial products and services of UPN Veteran Jawa Timur students. This study aims to analyze and design an entrepreneurial information system as a marketplace for business units of UPN Veteran Jawa Timur students and alumni. This study uses the waterfall model as a software development that assist in understanding the specifications of entrepreneurship information system requirements. The results of the analysis and design of the Entrepreneurship Information System is a solution for encouraging and facilitating the potential of entrepreneurial activities in UPN Veteran Jawa Timur students and alumni. Student entrepreneurship information system can be an icon for UPN Veteran Jawa Timur as a marketplace for online business units thereby increasing economic opportunities for UPN Veteran Jawa Timur students-alumni.